SARS-CoV-2 Infection in Children - Franchi Prato, Luis Miguel (2020)
At the end of 2019 a Coronavirus Disease 19 (COVID-19) pandemic starts in Asia. This disease arrives in Peru in March 202 affecting mainly adults but also children. The current available information indicates that children are as susceptible as adults to get this disease, generally from another household member, being asymptomatic in most cases but maintaining the capability of transmitting the virus to other persons. Adults, on the other side, acquire the disease from the community and have more severe symptoms. In this article we review the epidemiological and clinical characteristics of the disease and its treatment in patients under 18 years of age.